Synthesis and Evaluation of Cyromazine Molecularly Imprinted Polymeric Microspheres by Two-Step Seed Swelling Polymerization - Zhang, Yi-Jun; Feng, Rui; Qi, Na; Zhang, Yu-Ping; Bai, Lian-Yang; Huang, Ming-Xian (Asian Journal of Chemistry, 2013)
A novel cyromazine molecularly imprinted polymeric microspheres were prepared by two-step seed swelling polymerization method in aqueous system. The imprinting process was carried out using polystyrene particles as the seed, cyromazine as the template molecule, methacrylic acid as the functional monomer, ethylene glycol dimethacrylate as the cross-linker. Factors affecting the particle morphologies including emulsifier, dispersant, the water-oil ratio and etc., were optimized in order to obtain the molecularly imprinted polymeric microspheres with a final narrow particle diameter of 3-5 μm. The prepared molecularly imprinted polymeric microspheres were characterized and evaluated by scanning electron microscope, infrared absorption spectroscopy, mercury analyzer and equilibrium binding experiments, respectively. Scatchard analysis suggested cyromazine were recognized by the prepared molecularly imprinted polymeric microspheres with two classes of binding sites. The apparent maximum binding capacity and dissociation constant were calculated to be 1.25 μmol/g (Qmax1) and 1.27 μmol/L (Kd1) for high affinity site, whilst to be 2.84 μmol/g (Qmax2) and 10.02 μmol/L (Kd2) for low affinity site, respectively. The cyromazine molecularly imprinted polymeric microspheres synthesised in this method could be used as a stationary phase for the selective analysis of cyromazine in real samples by high performance liquid chromatography.